Ultralow-sheet-resistance ITO film and preparation method thereof

By plating the ITO layer twice and controlling the thickness and molar ratio of each layer, the problems of high square resistance and warping of the ITO film are solved, and the ITO film with low square resistance and high conductivity are achieved, which is suitable for automotive color-changing dimming films. Improves energy saving and reaction speed.

CN119217834AActive Publication Date: 2024-12-31ZHEJIANG RIJIU NEW MATERIAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411352538.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The square resistance of the existing ITO film is high, making it difficult to achieve ultra-low square resistance, and it is easy to cause the film surface to warp during the preparation process, affecting the resistance and conductivity.

Method used

The ITO layer is plating twice, and the thickness of the ITO layer is controlled between 50 and 250 nm for each plating. Combined with the silicon-aluminum mixed layer and the base layer, the indium-tin molar ratio and silicon-aluminum molar ratio are controlled to reduce the plating stress and promote the Crystal growth and carrier mobility improve conductivity.

Benefits of technology

The low square resistance and low warpage of the ITO film are achieved, the conductivity and usage performance are improved, and the energy consumption and dimming reaction speed are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119217834A_ABST
    Figure CN119217834A_ABST
Patent Text Reader

Abstract

The invention discloses an ultralow-sheet-resistance ITO film and a preparation method thereof. The ultralow-sheet-resistance ITO film comprises a base material layer, and an upper coating layer, a base layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially stacked on the base material layer; the thickness of the first ITO layer ranges from 50 nm to 250 nm, and the thickness of the second ITO layer ranges from 50 nm to 150 nm. The ultralow-sheet-resistance ITO film disclosed by the invention has relatively low sheet resistance, relatively low warping deformation and excellent use performance, and has the advantages of low resistance value, low energy consumption, energy conservation and high dimming reaction speed when being applied to an automobile color-variable dimming film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ITO films, and in particular relates to an ultra-low square resistance ITO film and a preparation method thereof. Background Art

[0002] Car color-changing dimming film refers to the optical properties of the material that can stably and reversibly change color under the action of an external electric field. This color-changing dimming function plays an important role in improving car driving experience, enhancing driver and passenger comfort, and adjusting the brightness of the car. It can automatically or manually control the car glass according to ambient light or user needs, and can dynamically change its optical and thermal properties to achieve the purpose of energy saving and comfortable visual experience.

[0003] The application of ITO film, i.e. indium tin oxide film, in electrochromic dimming film is mainly reflected in its use as a transparent electrode. As an electrode, ITO film can control the transparency or reflectivity of electrochromic dimming film by changing voltage or current, thereby realizing the dimming function. In order to improve the dimming reaction speed and reduce energy consumption, the lower the square resistance of ITO film, the more conducive it is to change voltage or current. However, the square resistance of existing ITO film is generally 12-20Ω. It is difficult to further reduce the square resistance of ITO film. Therefore, how to prepare ITO film with lower square resistance is a problem that needs to be solved at present.

[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0005] The object of the present invention is to provide an ultra-low square resistance ITO film and a preparation method thereof. The ultra-low square resistance ITO film has low square resistance, low warping and excellent use performance.

[0006] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:

[0007] An ultra-low square resistance ITO film comprises a substrate layer, on which an upper coating layer, a primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially stacked;

[0008] The thickness of the first ITO layer is 50-250 nm, and the thickness of the second ITO layer is 50-150 nm.

[0009] In one or more embodiments of the present invention, the molar ratio of indium to tin in the first ITO layer is (80-99): (1-20) based on indium to tin atoms.

[0010] In one or more embodiments of the present invention, the molar ratio of indium to tin in the second ITO layer is (80-99): (1-20) based on indium to tin atoms.

[0011] In one or more embodiments of the present invention, the molar ratio of silicon to aluminum in the silicon-aluminum mixed layer is (75-99): (1-25) based on silicon and aluminum atoms.

[0012] In one or more embodiments of the present invention, the thickness of the silicon-aluminum mixed layer is 1 to 30 nm.

[0013] In one or more embodiments of the present invention, the base layer material is selected from SiO2, Ti, TiO2, Si, Al2O3, MgF2, SiO, HfO2, SnO2 and Y2O3.

[0014] In one or more embodiments of the present invention, the thickness of the primer layer is 0.2-20 nm.

[0015] In one or more embodiments of the present invention, the substrate layer is a PET layer, a PI layer, a TAC layer, a COP layer or a PC layer.

[0016] Another specific embodiment of the present invention provides a technical solution as follows:

[0017] The method for preparing an ultra-low square resistance ITO film comprises the following steps:

[0018] Taking a substrate layer, coating an upper coating layer and a lower coating layer on both sides of the substrate layer respectively, and setting a high temperature protective film on the lower coating layer;

[0019] A primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially plated on the upper coating layer;

[0020] A positive protective film is provided on the second ITO layer.

[0021] In one or more embodiments of the present invention, the vacuum degree during plating is 1×10 -4 Pa or less, the water vapor value is 9×10 -5 Below pa, the reaction gas is a mixed gas of argon, nitrogen and oxygen, and the flow ratio of argon, nitrogen and oxygen is (60-80):(20-35):(5-10).

[0022] Compared with the prior art, the present invention reduces the possibility of stress release of the coating layer being affected by secondary plating of the ITO layer and controls the thickness of the ITO layer plated each time, promotes sufficient aging and crystallization of the coating layer, ensures the carrier concentration and mobility, and thus achieves the effect of low square resistance and high conductivity. When the ITO film in the present invention is used in the automotive color-changing dimming film, it has the advantages of low resistance, low energy consumption, and energy saving, and also effectively accelerates the dimming reaction speed. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 Schematic diagram of the structure of an ultra-low square resistance ITO film in one embodiment of the present invention.

[0025] Description of main reference numerals:

[0026] 1. High temperature protective film; 2. Lower coating layer; 3. Substrate layer; 4. Upper coating layer; 5. Primer layer; 6. Silicon-aluminum mixed layer; 7. First ITO layer; 8. Second ITO layer; 9. Positive protective film. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0028] Generally speaking, the thicker the ITO layer in the ITO film, the lower the resistance of the ITO film. In the preparation process of the ITO film, multiple pairs of indium tin targets are generally used for simultaneous plating. However, the heat is high during plating, which can easily cause the film surface to warp heavily and thus increase resistance. In order to pursue low resistance, the thickness of the ITO layer is generally thicker, such as 300nm and 400nm. The thicker thickness has a negative impact on the stress release of the coating, which will cause the ITO layer to be insufficiently crystallized during the aging crystallization process, and the square resistance uniformity is poor, so that it is impossible to obtain an ITO film with a lower square resistance.

[0029] The present invention modifies the method of plating a thicker ITO layer once into plating the ITO layer twice, and the thickness of the ITO layer plated each time is less than 300nm. The prepared ITO film not only has lower square resistance, but also has only extremely low warping on the film surface, high film formation rate and excellent performance.

[0030] A specific embodiment of the present invention provides an ultra-low square resistance ITO film, such as Figure 1As shown, it includes a substrate layer 3, on which an upper coating layer 4, a base layer 5, a silicon-aluminum mixed layer 6, a first ITO layer 7 and a second ITO layer 8 are sequentially stacked, the thickness of the first ITO layer 7 is 50 to 250 nm, and the thickness of the second ITO layer 8 is 50 to 150 nm.

[0031] Specifically, the ITO layer is plated twice, and the thickness of each ITO layer is controlled at the same time to reduce the accumulation of internal stress in the ITO layer, promote the crystal growth of the ITO layer, and make it fully crystallized, thereby reducing the problem of warping of the film layer due to deformation, and at the same time improve the conductivity of the ITO film, so that it has a lower square resistance.

[0032] In a specific embodiment, the molar ratio of indium tin in the first ITO layer 7 is (80-99):(1-20) based on indium tin atoms, and the molar ratio of indium tin in the second ITO layer 8 is (80-99):(1-20) based on indium tin atoms.

[0033] Specifically, the main factors affecting the conductive properties of the ITO layer are the carrier concentration and the carrier mobility. By controlling the indium-tin molar ratio, the carrier concentration can be increased. At the same time, the microstructure of the ITO layer can be optimized, and the carrier mobility can be improved, thereby reducing the resistivity of the ITO layer and making the ITO film present a lower square resistance.

[0034] In one specific embodiment, the molar ratio of silicon to aluminum in the silicon-aluminum mixed layer 6 is (75-99): (1-25) based on silicon and aluminum atoms.

[0035] In a specific embodiment, the thickness of the silicon-aluminum mixed layer 6 is 1-30 nm.

[0036] Specifically, the silicon-aluminum mixed layer 6 can reduce color difference and improve the weather resistance of the ITO film. When coating the silicon-aluminum mixed layer 6, the stability during sputtering can be improved by using a silicon-aluminum mixed target with a certain silicon-aluminum mixed ratio, making the sputtering more uniform, thereby obtaining a silicon-aluminum mixed layer 6 with a better microstructure, thereby improving the adhesion and photoelectric properties of the film layer.

[0037] In one specific embodiment, the material of the base layer 5 is selected from SiO2, Ti, TiO2, Si, Al2O3, MgF2, SiO, HfO2, SnO2 and Y2O3.

[0038] In one specific embodiment, the thickness of the primer layer 5 is 0.2-20 nm.

[0039] Specifically, selecting the above-mentioned types of primer layers 5 can increase the adhesion of the film layer, improve the stability of the film layer, and to a certain extent adjust the internal stress of the film layer, reduce the possibility of warping of the film layer, and improve the conductive performance.

[0040] In one specific embodiment, the substrate layer 3 is a PET layer, a PI layer, a TAC layer, a COP layer or a PC layer.

[0041] In one specific embodiment, the substrate layer 3 has a thickness of 5.7-250 μm.

[0042] Specifically, selecting the above types of substrate layer 3 can ensure the mechanical strength of the ITO film and ensure that it has better mechanical stability.

[0043] Another specific embodiment of the present invention provides a method for preparing an ultra-low square resistance ITO film, comprising the following steps 1-3.

[0044] Step 1: Take a substrate layer, coat an upper coating layer and a lower coating layer on both sides of the substrate layer respectively, and set a high-temperature protective film on the lower coating layer.

[0045] Specifically, the upper coating layer and the lower coating layer are both formed by coating an acrylic resin coating liquid, which is a conventional product used to improve the corrosion resistance and weather resistance of the film material. Preferably, the thickness of the upper coating layer is 40 to 900 nm, and the thickness of the lower coating layer is 20 to 900 nm. The high-temperature protective film is a PET film with a thickness of 30 to 188 μm. The high-temperature protective film is provided on the lower coating layer to protect the appearance of the film surface and improve the stability of the coating during the subsequent magnetron sputtering coating process.

[0046] Step 2: sequentially plate a primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer on the upper coating layer.

[0047] Specifically, during plating, the vacuum degree is 1×10 -4 Pa or less, the water vapor value is 9×10 -5 Below pa, the reaction gas is a mixture of argon, nitrogen and oxygen, and the flow ratio of argon, nitrogen and oxygen is (60-80): (20-35): (5-10). By controlling the vacuum degree, water vapor value and reaction gas, the sputtering uniformity can be improved and the optical stability after the film layer is stacked can be improved.

[0048] Step 3, setting a positive protective film on the second ITO layer.

[0049] Specifically, the positive protective film is a PET film.

[0050] The present invention is further described in detail below in conjunction with specific embodiments.

[0051] Example 1

[0052] The ultra-low square resistance ITO film includes, from bottom to top, a stacked PET high temperature protective film of 30 μm, a lower coating layer of 60 nm, a PET substrate layer of 38 μm, an upper coating layer of 40 nm, a SiO2 base layer of 10 nm, a silicon-aluminum mixed layer of 5 nm, a first ITO layer of 100 nm, a second ITO layer of 100 nm, and a PET positive protective film of 40 μm. The silicon-aluminum molar ratio in the silicon-aluminum mixed layer is 75:25 in terms of silicon-aluminum atoms, the indium-tin molar ratio in the first ITO layer is 99:1 in terms of indium-tin atoms, and the indium-tin molar ratio in the second ITO layer is 99:1 in terms of indium-tin atoms.

[0053] During the preparation, acrylic resin coating liquid is coated on both sides of the PET substrate layer, and after drying, an upper coating layer and a lower coating layer are formed, and a PET high-temperature protective film is attached to the lower coating layer; then, dry magnetron vacuum coating sputtering is used, and the vacuum degree is controlled to be 1×10 -4 Pa or less, water vapor value 9×10 -5 Below pa, a mixed gas of argon, nitrogen and oxygen is selected as the reaction gas, and the flow ratio of argon, nitrogen and oxygen is 60:30:10. SiO2 primer layer, silicon-aluminum mixed layer, first ITO layer and second ITO layer are deposited on the upper coating layer in sequence. After the deposition, the film material is placed in an oven at 150°C for aging and crystallization for 5 minutes. Finally, a PET positive protective film is attached to the second ITO layer to obtain an ultra-low square resistance ITO film.

[0054] Example 2

[0055] The ultra-low square resistance ITO film includes, from bottom to top, a stacked PET high temperature protective film of 70 μm, a lower coating layer of 160 nm, a PET substrate layer of 80 μm, an upper coating layer of 200 nm, a SiO2 base layer of 15 nm, a silicon-aluminum mixed layer of 10 nm, a first ITO layer of 150 nm, a second ITO layer of 100 nm, and a PET positive protective film of 40 μm. The silicon-aluminum molar ratio in the silicon-aluminum mixed layer is 99:1 in terms of silicon-aluminum atoms, the indium-tin molar ratio in the first ITO layer is 80:20 in terms of indium-tin atoms, and the indium-tin molar ratio in the second ITO layer is 80:20 in terms of indium-tin atoms.

[0056] During the preparation, acrylic resin coating liquid is coated on both sides of the PET substrate layer, and after drying, an upper coating layer and a lower coating layer are formed, and a PET high-temperature protective film is attached to the lower coating layer; then, dry magnetron vacuum coating sputtering is used, and the vacuum degree is controlled to be 1×10 -4 Pa or less, water vapor value 9×10 -5Below pa, a mixed gas of argon, nitrogen and oxygen is selected as the reaction gas, and the flow ratio of argon, nitrogen and oxygen is 60:30:10. SiO2 primer layer, silicon-aluminum mixed layer, first ITO layer and second ITO layer are deposited on the upper coating layer in sequence. After the deposition, the film material is placed in an oven at 150°C for aging and crystallization for 5 minutes. Finally, a PET positive protective film is attached to the second ITO layer to obtain an ultra-low square resistance ITO film.

[0057] Example 3

[0058] The ultra-low square resistance ITO film includes, from bottom to top, a stacked PET high-temperature protective film of 160 μm, a lower coating layer of 300 nm, a PET substrate layer of 100 μm, an upper coating layer of 400 nm, a SiO2 base layer of 20 nm, a silicon-aluminum mixed layer of 20 nm, a first ITO layer of 150 nm, a second ITO layer of 150 nm, and a PET positive protective film of 40 μm. The silicon-aluminum molar ratio in the silicon-aluminum mixed layer is 75:25 based on silicon-aluminum atoms, the indium-tin molar ratio in the first ITO layer is 87:13 based on indium-tin atoms, and the indium-tin molar ratio in the second ITO layer is 87:13 based on indium-tin atoms.

[0059] During the preparation, acrylic resin coating liquid is coated on both sides of the PET substrate layer, and after drying, an upper coating layer and a lower coating layer are formed, and a PET high-temperature protective film is attached to the lower coating layer; then, dry magnetron vacuum coating sputtering is used, and the vacuum degree is controlled to be 1×10 -4 Pa or less, water vapor value 9×10 -5 Below pa, a mixed gas of argon, nitrogen and oxygen is selected as the reaction gas, and the flow ratio of argon, nitrogen and oxygen is 60:30:10. SiO2 primer layer, silicon-aluminum mixed layer, first ITO layer and second ITO layer are deposited on the upper coating layer in sequence. After the deposition, the film material is placed in an oven at 150°C for aging and crystallization for 5 minutes. Finally, a PET positive protective film is attached to the second ITO layer to obtain an ultra-low square resistance ITO film.

[0060] Example 4

[0061] The ultra-low square resistance ITO film includes, from bottom to top, a stacked PET high temperature protective film of 130 μm, a lower coating layer of 500 nm, a PET substrate layer of 125 μm, an upper coating layer of 600 nm, a SiO2 base layer of 20 nm, a silicon-aluminum mixed layer of 30 nm, a first ITO layer of 250 nm, a second ITO layer of 150 nm, and a PET positive protective film of 40 μm. The silicon-aluminum molar ratio in the silicon-aluminum mixed layer is 99:1 based on silicon-aluminum atoms, the indium-tin molar ratio in the first ITO layer is 95:5 based on indium-tin atoms, and the indium-tin molar ratio in the second ITO layer is 95:5 based on indium-tin atoms.

[0062] During the preparation, acrylic resin coating liquid is coated on both sides of the PET substrate layer, and after drying, an upper coating layer and a lower coating layer are formed, and a PET high-temperature protective film is attached to the lower coating layer; then, dry magnetron vacuum coating sputtering is used, and the vacuum degree is controlled to be 1×10 -4 Pa or less, water vapor value 9×10 -5 Below pa, a mixed gas of argon, nitrogen and oxygen is selected as the reaction gas, and the flow ratio of argon, nitrogen and oxygen is 60:30:10. SiO2 primer layer, silicon-aluminum mixed layer, first ITO layer and second ITO layer are deposited on the upper coating layer in sequence. After the deposition, the film material is placed in an oven at 150°C for aging and crystallization for 5 minutes. Finally, a PET positive protective film is attached to the second ITO layer to obtain an ultra-low square resistance ITO film.

[0063] Comparative Example 1

[0064] The ultra-low square resistance ITO film includes, from bottom to top, a stacked PET high temperature protective film of 30μm, a lower coating layer of 60nm, a PET substrate layer of 38μm, an upper coating layer of 40nm, a SiO2 base layer of 10nm, a silicon-aluminum mixed layer of 5nm, an ITO layer of 300nm, and a PET positive protective film of 40μm. The silicon-aluminum molar ratio in the silicon-aluminum mixed layer is 75:25 based on silicon-aluminum atoms, and the indium-tin molar ratio in the ITO layer is 99:1 based on indium-tin atoms.

[0065] During the preparation, acrylic resin coating liquid is coated on both sides of the PET substrate layer, and after drying, an upper coating layer and a lower coating layer are formed, and a PET high-temperature protective film is attached to the lower coating layer; then, dry magnetron vacuum coating sputtering is used, and the vacuum degree is controlled to be 1×10 -4 Pa or less, water vapor value 9×10 -5 Below pa, a mixed gas of argon, nitrogen and oxygen is selected as the reaction gas, and the flow ratio of argon, nitrogen and oxygen is 60:30:10. SiO2 primer layer, silicon-aluminum mixed layer and ITO layer are deposited on the upper coating layer in sequence. After the deposition, the film material is placed in an oven at 150°C for aging and crystallization for 5 minutes. Finally, a PET positive protective film is attached to the ITO layer to obtain an ultra-low square resistance ITO film.

[0066] Comparative Example 2

[0067] The ultra-low square resistance ITO film includes, from bottom to top, a stacked PET high temperature protective film of 70μm, a lower coating layer of 160nm, a PET substrate layer of 80μm, an upper coating layer of 200nm, a SiO2 base layer of 15nm, a silicon-aluminum mixed layer of 10nm, an ITO layer of 300nm, and a PET positive protective film of 40μm. The silicon-aluminum molar ratio in the silicon-aluminum mixed layer is 99:1 based on silicon-aluminum atoms, and the indium-tin molar ratio in the ITO layer is 80:20 based on indium-tin atoms.

[0068] During the preparation, acrylic resin coating liquid is coated on both sides of the PET substrate layer, and after drying, an upper coating layer and a lower coating layer are formed, and a PET high-temperature protective film is attached to the lower coating layer; then, dry magnetron vacuum coating sputtering is used, and the vacuum degree is controlled to be 1×10 -4 Pa or less, water vapor value 9×10 -5 Below pa, a mixed gas of argon, nitrogen and oxygen is selected as the reaction gas, and the flow ratio of argon, nitrogen and oxygen is 60:30:10. SiO2 primer layer, silicon-aluminum mixed layer and ITO layer are deposited on the upper coating layer in sequence. After the deposition, the film material is placed in an oven at 150°C for aging and crystallization for 5 minutes. Finally, a PET positive protective film is attached to the ITO layer to obtain an ultra-low square resistance ITO film.

[0069] Comparative Example 3

[0070] The ultra-low square resistance ITO film includes, from bottom to top, a stacked PET high-temperature protective film of 160 μm, a lower coating layer of 300 nm, a PET substrate layer of 100 μm, an upper coating layer of 400 nm, a SiO2 base layer of 20 nm, a silicon-aluminum mixed layer of 20 nm, an ITO layer of 300 nm, and a PET positive protective film of 40 μm. The silicon-aluminum molar ratio in the silicon-aluminum mixed layer is 75:25 based on silicon-aluminum atoms, and the indium-tin molar ratio in the ITO layer is 87:13 based on indium-tin atoms.

[0071] During the preparation, acrylic resin coating liquid is coated on both sides of the PET substrate layer, and after drying, an upper coating layer and a lower coating layer are formed, and a PET high-temperature protective film is attached to the lower coating layer; then, dry magnetron vacuum coating sputtering is used, and the vacuum degree is controlled to be 1×10 -4 Pa or less, water vapor value 9×10 -5 Below pa, a mixed gas of argon, nitrogen and oxygen is selected as the reaction gas, and the flow ratio of argon, nitrogen and oxygen is 60:30:10. SiO2 primer layer, silicon-aluminum mixed layer and ITO layer are deposited on the upper coating layer in sequence. After the deposition, the film material is placed in an oven at 150°C for aging and crystallization for 5 minutes. Finally, a PET positive protective film is attached to the ITO layer to obtain an ultra-low square resistance ITO film.

[0072] Comparative Example 4

[0073] The ultra-low square resistance ITO film includes, from bottom to top, a stacked PET high temperature protective film of 130 μm, a lower coating layer of 500 nm, a PET substrate layer of 125 μm, an upper coating layer of 600 nm, a SiO2 base layer of 20 nm, a silicon-aluminum mixed layer of 30 nm, an ITO layer of 400 nm, and a PET positive protective film of 40 μm. The silicon-aluminum molar ratio in the silicon-aluminum mixed layer is 99:1 based on silicon-aluminum atoms, and the indium-tin molar ratio in the ITO layer is 95:5 based on indium-tin atoms.

[0074] During the preparation, acrylic resin coating liquid is coated on both sides of the PET substrate layer, and after drying, an upper coating layer and a lower coating layer are formed, and a PET high-temperature protective film is attached to the lower coating layer; then, dry magnetron vacuum coating sputtering is used, and the vacuum degree is controlled to be 1×10 -4 Pa or less, water vapor value 9×10 -5 Below pa, a mixed gas of argon, nitrogen and oxygen is selected as the reaction gas, and the flow ratio of argon, nitrogen and oxygen is 60:30:10. SiO2 primer layer, silicon-aluminum mixed layer and ITO layer are deposited on the upper coating layer in sequence. After the deposition, the film material is placed in an oven at 150°C for aging and crystallization for 5 minutes. Finally, a PET positive protective film is attached to the ITO layer to obtain an ultra-low square resistance ITO film.

[0075] The following performance tests were performed on the ultra-low square resistance ITO films in each embodiment and each comparative example:

[0076] (1) After the plating is completed and the machine is removed, 10 points are taken on average according to the film width and the square resistance of the 10 points is tested before and after aging and crystallization. The film width is 1200mm. During the test, the film material is placed flat on the table with the film surface facing up. The surface square resistance is tested with a square resistance meter. After aging and crystallization, the resistance value is required to reach 8±2Ω. The results are shown in Table 1.

[0077] (2) After the coating is completed and the machine is removed, three samples are cut according to the average film width, with a sample size of 340*340mm. The samples are baked in a 150℃ oven for 5 minutes. After the baking is completed, wait until the temperature drops below 70℃, take out the samples, place the sample film surface facing up on the table, and use a ruler to measure the upward warping height of the four corners. Then, place the film material on the back and use a ruler to measure the downward warping height of the four corners. The upward warping height is required to be ≤20mm and the downward warping height is ≤-10mm. The results are shown in Table 2.

[0078] Table 1 ITO film square resistance test results

[0079]

[0080]

[0081] Note: The unit in Table 1 is Ω.

[0082] Table 2 ITO film warping results

[0083]

[0084]

[0085] Note: The unit in Table 2 is mm.

[0086] Combined with Table 1, in Comparative Examples 1 to 4, the ITO layer is plated once, and the average resistance value of the obtained film material after aging and crystallization is as low as 9.4Ω and as high as 11.5Ω, which obviously does not meet the 8±2Ω requirement. However, the average resistance value of the ITO film after aging and crystallization in the embodiment of the present invention is as low as 8.1Ω and as high as 8.2Ω, reaching the target square resistance, indicating that the present invention can effectively ensure that the final ITO film has a lower square resistance by plating a certain thickness of ITO layer twice.

[0087] Combined with Table 2, the average upward warping height of the ITO film in Comparative Examples 1 to Comparative Examples 4 is as low as 35 mm and as high as 51 mm, and the average downward warping height is as low as -19 mm and as high as -31 mm. The average upward warping height of the ITO film in the present invention is as low as 7 mm and as high as 9 mm, and the average downward warping height is -2 mm, which meets the requirements of upward warping height ≤20 mm and downward warping height ≤-10 mm, further illustrating that the present invention can effectively reduce the problem of warping of the film material by plating the ITO layer twice and controlling the thickness of the ITO, thereby ensuring low square resistance and low warping of the final ITO film.

[0088] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0089] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. An ultra-low square resistance ITO film, characterized in that: It comprises a substrate layer, on which an upper coating layer, a primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially stacked; The thickness of the first ITO layer is 50-250 nm, and the thickness of the second ITO layer is 50-150 nm.

2. The ultra-low square resistance ITO film according to claim 1, characterized in that: The molar ratio of indium to tin in the first ITO layer is (80-99): (1-20) based on indium tin atoms.

3. The ultra-low square resistance ITO film according to claim 1, characterized in that: The molar ratio of indium to tin in the second ITO layer is (80-99): (1-20) based on indium tin atoms.

4. The ultra-low square resistance ITO film according to claim 1, characterized in that: The molar ratio of silicon to aluminum in the silicon-aluminum mixed layer is (75-99): (1-25) based on silicon and aluminum atoms.

5. The ultra-low square resistance ITO film according to claim 1, characterized in that: The thickness of the silicon-aluminum mixed layer is 1-30 nm.

6. The ultra-low square resistance ITO film according to claim 1, characterized in that: The base layer material is selected from SiO2, Ti, TiO2, Si, Al2O3, MgF2, SiO, HfO2, SnO2 and Y2O3.

7. The ultra-low square resistance ITO film according to claim 1, characterized in that: The thickness of the base layer is 0.2-20 nm.

8. The ultra-low square resistance ITO film according to claim 1, characterized in that: The substrate layer is a PET layer, a PI layer, a TAC layer, a COP layer or a PC layer.

9. The method for preparing the ultra-low square resistance ITO film according to any one of claims 1 to 8, characterized in that: The following steps are involved: Taking a substrate layer, coating an upper coating layer and a lower coating layer on both sides of the substrate layer respectively, and setting a high temperature protective film on the lower coating layer; A primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially plated on the upper coating layer; A positive protective film is provided on the second ITO layer.

10. The method for preparing the ultra-low square resistance ITO film according to claim 9, characterized in that: During plating, the vacuum degree is 1×10 -4 Pa or less, the water vapor value is 9×10 -5 Below pa, the reaction gas is a mixed gas of argon, nitrogen and oxygen, and the flow ratio of argon, nitrogen and oxygen is (60-80):(20-35):(5-10).

Citation Information

Patent Citations

  • Transparent conductive film and touch panel

    CN109215847A

  • Low-square-resistance and low-chromatic-aberration type dimming film and preparation method thereof

    CN115826271A

  • Low-reflection and low-transmission optical thin film with ink layer and preparation method of low-reflection and low-transmission optical thin film

    CN118483775A

  • AR film and preparation method thereof

    CN118625422A

  • Flexible film with high reflection and preparation method

    CN118688889A